Prevalence of postpartum depression in patients with migraine - Reis , Ana Clara Sfredo dos Santos e; Gonçalves, Ana Luiza Rodegheri; Santos, Bruna Oliveira Rodrigues dos; Silva , Júlia Milan Procópio e; Câmara, Lorenza de Ávila Gomes Carneiro Dutra; Jurno, Mauro Eduardo (Headache Medicine, 2022)
Introduction Migraine is a disease of the central nervous system characterized by moderate or severe headache. Migraine is considered the third most prevalent disease and the seventh specific cause of incapacity in the world. The prevalence of migraine in women increase after menarche compared with the prevalence of migraine in men. According to previous population-based studies, during reproductive years, a woman who has the diagnosis of menstrual migraine experiences the same symptoms throughout pregnancy and postpartum. Childbirth is a major event in a woman’s life. However, some mothers might present symptoms of postnatal depression. Postpartum depression is a mental disorder that reflects on the maternal role. Thus, it has negative consequences for them and their children. Postpartum depression is associated with increased risk for cognitive BB impairment, emotional difficulties and behavioral problems. Clinically, headache influences the mental and physical health of pregnant and postpartum women. Studies reported that anxiety and depression disorders are two to ten times more common in migraineurs than in the general population. Therefore, it can be a risk for postpartum depression development. Objective To verify postpartum depression in migraine and non-migraine parturients. Methods Data was collected from a sample of 155 women, older than 18 years old, in the obstetric center of Santa Casa de Misericórdia de Barbacena, between October 2021 and August 2022, in the first 24 hours after labor by the members of the research. Clinic and concomitant disorders were collected from the patient's record. Parturients who did not agree to participate in the study and those with cognitive impairment were excluded. All the patients signed an informed consent form to participate in the study. All the patients answered the Edinburgh Postnatal Depression Scale (EPDS) and the ID-Migraine... (To see the complet abstract, please, check out the PDF.)